Effectiveness of Content – Based Instructionin Improving Students’ Islamic Writing Ability In Islamic Boarding School of Al-Wahid Papesidenrengrappang: Effectiveness of Content – Based Instructionin Improving Students’ Islamic Writing Ability In Islamic Boarding School of Al-Wahid Papesidenrengrappang - Haseng, Amran; Latifa, Ammang; Rahman, Abdul (La Parole : Journal of Language Teaching and Pedagogy, 2021)
This research is aimed at finding out: How isthe effectiveness of Content - Based Instruction in improving the students’ writing ability of the tenth year students.To achieve the goal of this study. The researcher did experimental research was used as a method in this study and research design used was a quasi experimental. The study was carried out in two classes, they are the experimental group and controlgroup. The population of this research were the tenth class of Al-Wahid Papein academic year 2018-2019. X MIA was chosen as the experimental group and X IIS were chosen as the control group. The instruments for collecting the data were writing test, questionnaire, and observation sheet. The data obtained through the test were analyzed qualitatively and quantitatively.Based on the resultof the data analysis, the researcher finding shows that the students’ writing ability of the experimental group has a significan different from the control group. The students could developing and generate their ideas bycontent-based instruction and make the students more enthusiastic in the writing activities. All students could understand and respond to the researcher’ instructions and explanations. It is proved by the data that the mean score of the experimental group is higher than control group ( 76.18 > 60.32), and the t-test value is higher than t-table value ( 4.905> 1.685). The result of this study indicates that the use of content-based instruction significantly improves the students writing ability. The researcher finding that the students’ have positive attitude toward the use of content-based instruction. It is proved by the data from questionnaire that the students’ mean score of attitude is 102.21, which is categorized as very high, and the data from observation sheet that the percentage of positive items is higher that negative items ( 89.3 > 53,9 ).